The Multiple Sclerosis Inventory of Cognition for Adolescents (MUSICADO): A brief screening instrument to assess cognitive dysfunction, fatigue and loss of health-related quality of life in pediatric-onset multiple sclerosis. (November 2019) - ,; Kraus, V.; Dornfeld, E.; Elpers, C.; Lohmann, H.; Weddige, A.; Hagspiel, S.; Kirschner, J.; Brehm, M.; Blank, C.; Schubert, J.; Schimmel, M.; et al.
Abstract: Objective: Screening for cognitive impairment (CI), fatigue and also Health-related quality of life (HRQoL) in patients with pediatric-onset multiple sclerosis (POMS) is of utmost importance in clinical practice. The aim of this study was to establish a new and validated pediatric screening tool "MUSIC ADO " that is easy to use and time economical. Methods: 106 patients with POMS aged 12–18 years and 210 healthy controls (HCs) stratified for age and education underwent neuropsychological testing including a screening test "Multiple Sclerosis Inventory of Cognition" for adults and 8 standardized cognitive tests and established scales to assess fatigue and HRQoL. Results: The phonemic verbal fluency task (RWT "s-words"), the Trail Making Test A (TMT-A), and the Digit Span Forward discriminated significantly between patients and HCs ( p  = 0.000, respectively) and showed the highest proportion of test failure in patients (24.5%, 17.9%; 15.1%, respectively). Therefore, they were put together to form the cognitive part of the "MUSIC ADO ". After applying a scoring algorithm with balanced weighting of the subtests and age and education correction and a cut-off score for impairment, 35.8% of patients were categorized to be cognitively impaired (specificity: 88.6%). Fatigue was detected in 37.1% of the patients (specificity: 94.0%) and loss of HRQoL in 41.8% (specificity 95.7%) with the screening version, respectively. Conclusion: The MUSIC ADO is a newly designed brief and easy to use screening test to help to early identify CI, fatigue, and loss of HRQoL in patients with POMS as cut scores are provided for all three items. Further studies will have to show its usability in independent samples of patients with POMS. Highlights: A screening tool for pediatric patients with multiple sclerosis to detect cognitive impairment, fatigue and HRQoL. This screening tool considers an age and education correction to detect CI. Cut scores are provided to define CI, severity of fatigue and loss of HRQoL. 35.8% of patients were categorized to be cognitively impaired, 37.1% to be fatigued and loss of HRQoL in 41.8%.